1990
DOI: 10.1038/jcbfm.1990.64
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylthiourea Reduces Ischemic Brain Edema without Affecting Cerebral Blood Flow

Abstract: Summary: Oxygen free radicals have been implicated as mediators of tissue damage in ischemic brain . We previ ously demonstrated that the hydroxyl radical scavenger 1,3-dimethyl-2-thiourea (DMTU) reduces infarct size af ter middle cerebral artery occlusion (MCAO) in rats. The present study was undertaken to determine whether this protection results from a preservation of the CBP . Adult male Sprague-Dawley rats were treated with DMTU (750 mg/kg i. There is increasing evidence that oxygen free rad icals are imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The increase in BBB [ 3 H]AIB permeability after intracerebral infusion of lysed RBCs is also greater than that which occurs in focal cerebral ischemia, in which increases of 70% to 100% occur 24 hours after middle cerebral artery occlusion in the rat. 14,36 Similarly, we found that BBB inulin permeability is increased by a factor of 3 at 6 hours after middle cerebral artery occlusion, compared with an 11-fold increase induced by lysed RBCs reported in this study. 37 Because the adverse effect of an ICH seems to result from a "toxic" effect of blood components on the brain, the question arises as to whether clot removal is the best therapeutic strategy, because it would result in the removal of all the toxic components.…”
Section: Discussionsupporting
confidence: 52%
“…The increase in BBB [ 3 H]AIB permeability after intracerebral infusion of lysed RBCs is also greater than that which occurs in focal cerebral ischemia, in which increases of 70% to 100% occur 24 hours after middle cerebral artery occlusion in the rat. 14,36 Similarly, we found that BBB inulin permeability is increased by a factor of 3 at 6 hours after middle cerebral artery occlusion, compared with an 11-fold increase induced by lysed RBCs reported in this study. 37 Because the adverse effect of an ICH seems to result from a "toxic" effect of blood components on the brain, the question arises as to whether clot removal is the best therapeutic strategy, because it would result in the removal of all the toxic components.…”
Section: Discussionsupporting
confidence: 52%
“…942 In a previous study using ketamine/xylazine-anesthetized rats, cerebral blood flow was found to average 17 ml/100 g/min in the center zone, 26 ml/100 g/min in the intermediate zone, and 44 ml/100 g/min in the outer zone after 4 hours of ischemia. 9 The rats were divided into six groups: eight were treated with vehicle, seven with 375 mg/kg DMTU, eight with 750 mg/kg DMTU, eight with 0.5 mg/kg MK-801, seven with 2.0 mg/kg MK-801, and eight with both 750 mg/kg DMTU and 0.5 mg/kg MK-801. Since our previous experimental results showed that the water content of the nonischemic hemisphere was identical to that in sham-operated control rats, 9 ' 11 in the present study the sham-operated control group was omitted.…”
Section: Methodsmentioning
confidence: 99%
“…Three samples (ipsi-or contralateral) were taken from the remaining tissue using 5-and 7-mm cork borers (Dickinson and Betz, 1992;Martz et al, 1990). The core region was taken from the cortex and striatum underlying the MCA immediately distal to the region of occlusion (Fig.…”
Section: Measurement Of Brain Water and Ion Concentrationmentioning
confidence: 99%